Kesantunan berbahasa dalam buku Pemimpin dalam Ungkapan Melayu karya Tenas Effendy / Siti Noraien Razali - Siti Noraien, Razali (2016)
This dissertation discusses the politeness of language contained in the book Pemimpin dalam Ungkapan Melayu (2000) by Tenas Effendy. There are three objectives, namely to identify the characteristics of politeness of language contained in research material ; to analyze aspects of politeness of language in Malay expression; and to describe the values and lessons found in the research material. The politeness theory promoted by Leech (1993) was choosen as basis for research. Leech (1993) has listed six maxims, which are the tact maxim, the generosity maxim, the approvation maxim, the modesty maxim, the agreement maxim and the sympathy maxim. The book Pemimpin dalam Ungkapan Melayu (2000) written by Tenas Effendy was used as research material, and qualitative data analysis was used to get an effective result. This research will provide readers, especially the younger generation with information of politeness contained in Malay expression. The results of this research found that the book Pemimpin dalam Ungkapan Melayu (2000) by Tenas Effendy has a high level of characteristics of politeness. In addition, this research also provide example the values and lessons that will useful to the leaders and future leaders of the community.